Three-Way Chess - Krabbendam, Hans (Church history and religious culture, 2014)
By following the career and networks of Dutch missionary and diplomat Arie Kok (1883–1951), this essay explores the motives for creating a transatlantic fundamentalist network after World War II. Using private correspondence, interviews, institutional records, and periodicals, the essay demonstrates that the goal, means, and strategy of American fundamentalists tied them closely to other American Protestant groups active in postwar Europe. Apart from the exclusivist doctrine and antithetical style, which burdened the chances for positive cooperation among traditional Protestants, it was the national agenda of Carl McIntire, the American father of international fundamentalism that nullified Kok’s transnational endeavors. Despite these limitations, Kok succeeded briefly in captivating a group of Europeans, shaping the discourse and the religious activities of the Americans on the European continent, and causing the emerging evangelicals serious concern.